Effect of avermectin-containing drugs on wheat resistance to drought - Pushkarova, N.O.; Kvasko, A.Yu.; Buziashvili, A.Yu.; Kravets, O.A.; Chugunkova, T.V.; Blume, Ya.B.; Yemets, A.I. (Reports of the National Academy of Sciences of Ukraine, 2022)
The effect of avermectin-containing polyfunctional drugs on the wheat resistance to drought is studied. For this purpose, Avercom and Avercom Nova impact effectiveness on the growth and development of three Ukrainian wheat varieties (Elegia Myronivska, Oksamyt Myronivskuy and Zlata) under drought, particularly on growth medium containing 10 % PEG 6000, was determined. When growing wheat under drought conditions, Avercom and Avercom Nova were established for the first time to: 1) have positive effect on sprouts growth of all studied species, 2) induce plants root growth during germination at 4 days (the effect was more pronounced for Elegia Myronivska variety at 14 days with the use of Avercom), 3) lead to considerable increase of plants raw mass for Zlata variety at 14 days of growth. Therefore, obtained results indicate the protective effect of avermectin-containing drugs during wheat growth under stress conditions, particularly under simulated water deficiency conditions.